The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/or.2017.5813
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-131 induces apoptosis in human cardiac muscle cells through the p53/Bax/caspase-3 and PIDD/caspase-2/t-BID/cytochrome c/caspase-3 signaling pathway

Abstract: The aim of this study was to elucidate the effects of iodine-131 on the induction of apoptosis in human cardiac muscle cells and the underlying molecular mechanisms. We found that iodine-131 reduced cell proliferation, induced apoptosis, induced p53, PIDD, t-BID (mitochondria) protein expression, suppressed cytochrome c (mitochondria) protein expression, and increased Bax protein expression, and promoted caspase-2, -3 and -9 expression levels in human cardiac muscle cells. Meanwhile, si-p53 inhibited the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Caspase 2 (CASP2) may function in stress-induced cell death pathways, cell cycle maintenance and tumor suppression (13). CASP2 can induce apoptosis, and overexpression of CASP2 was previously demonstrated in several types of cells (14,15). CASP2 is regulated by several miRNAs, such as miR-183 in ovarian cancer (16).…”
Section: Introductionmentioning
confidence: 91%
“…Caspase 2 (CASP2) may function in stress-induced cell death pathways, cell cycle maintenance and tumor suppression (13). CASP2 can induce apoptosis, and overexpression of CASP2 was previously demonstrated in several types of cells (14,15). CASP2 is regulated by several miRNAs, such as miR-183 in ovarian cancer (16).…”
Section: Introductionmentioning
confidence: 91%
“…Cyclin D was expressed at the G1 Cyclin. Researchers had previously demonstrated that Bax/Bad mitochondrial translocation, up-regulation of p53, caspase-3 activation, PARP cleavage and DNA fragmentation were associated with apoptotic cell death in cardiomyocytes (Wang, Liu, Wang, Zhang and Chen, 2017). Punicalagin reduced H 2 O 2 -induced apoptosis by modulating the levels of reactive oxygen in PC12 cells (Clementi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Puma is a powerful proapoptotic protein that is able to inhibit the expression of the antiapoptotic protein Bcl-2 (32). If the balance between proapoptotic factors and antiapoptotic factors is altered, the permeability of the mitochondrial membrane increases and cytochrome c is released into the cytoplasm, thus activating the caspase cascade, which results in caspase-mediated breakdown of the mitochondrial membrane (33)(34)(35). Puma is transcriptionally activated by p53 (36,37).…”
Section: Discussionmentioning
confidence: 99%